Genotoxicity biomarkers for monitoring occupational exposure to antineoplastic drugs - Hilda M. Rodríguez-Montero; Esther Argote-Pelegrino; Adriana Díaz-Curbelo; Elizabeth B. Cuétara-Lugo (GarVal Editorial Ltda., 2016)
Context: The Institute of Oncology and Radiobiology (INOR) is the leading institution for the diagnosis, treatment and follow-up of cancer in Cuba. The main methods used in cancer treatment are surgery, radiotherapy and chemotherapy. The last one involves the handling of hazardous substances, such as cytostatics, which implies a health risk to persons occupationally exposed to it. There are two sites where a considerable among of cytostatic is handled (Ambulatory Chemotherapy Room (ACR) and the Central Unit of Cytostatic Mixture Preparation (CUCM)). Genotoxicity biomarkers of exposure and effects have been widely used to detect occupational environment hazards. Aims: To evaluate genotoxicity biomarkers indicative of exposure and effects to cytostatics. Methods: In this study were tested samples taken from the surfaces of biological safety cabinets located in the Central Unit of Cytostatic Mixture using SOS - Chromotest. We also evaluated samples of oral mucosa exfoliated cells from exposed and control subjects, by micronucleus test. Results: All subjects were exposed and subjects who administered the mixes in the institution had an increased of DNA damage in comparison with the pharmaceutical staff that prepared it and wear the primary protection barriers properly. Conclusions: These results underline the efficiency of genotoxicological biomarkers in detecting the exposure levels and the deleterious effect of cytostatics on occupationally exposed personal.